Legal Implementation of the Validity of Electronic Certificates - Syabbani, Maulana Zakki; Hasana, Dahniarti (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
The implementation of land certificate digitalization from analog certificates converted into electronic certificates is carried out in stages and using a pilot project system. The readiness of both human resources and infrastructure must truly meet the required standards. However, the process of certificate digitalization in Indonesia cannot be denied considering that one of its goals is to minimize land disputes and legal protection for land object owners. This study aims to determine the extent of the implementation of the validity of electronic certificates after the issuance of the Regulation of the Minister of ATR/BPN Number 1 of 2021 concerning Electronic Certificates in Bantul Regency. The approach method used in this thesis is empirical juridical. The specifications of this study use descriptive analysis. The type of data used in this study is primary data which includesCivil Code,Basic Agrarian Law (UUPA) Law Number 11 of 2020 concerning Job CreationRegulation of the Minister of ATR Number 1 of 2021 concerning Electronic Certificates, as well as secondary data containing books and other supporting documents. Collection of research data using interview techniques and document studies or library materials. The data analysis method used in analyzing the data is a qualitative analysis of the interactive model as proposed. The results of the study show that: First, the implementation of land certificate digitalization in Indonesia is gradual. The Bantul ATR/BPN Office is still in the process of processing electronic certificates for Government Offices. Second: Each office of each ATR/BPN is expected to have prepared various aspects such as caution.